The multiple actions of grape and its polyphenols on female reproductive processes with an emphasis on cell signalling - Kohut, Ladislav; Baldovska, Simona; Mihal, Michal; Belej, Lubomir; Sirotkin, Alexander V.; Roychoudhury, Shubhadeep; Kolesarova, Adriana (Frontiers in Endocrinology, 2024)
Grapes are an economically important fruit crop, and their polyphenols (mainly phenolic acids, flavanols, flavonols, anthocyanins, proanthocyanidins, and stilbenes) can exert a wide range of health benefits as an interesting and valuable dietary supplement for natural complementary therapy. However, their potential physiological and therapeutic actions on reproductive processes have not been sufficiently elucidated. This evidence-based study presents current knowledge of grape extracts and polyphenols, as well as their properties and therapeutical actions in relation to female reproduction in a nutshell. Grape extract, and its polyphenols such as resveratrol, proanthocyanidin B2 or delphinidin may influence female reproductive physiology and pathology, as well as regulate multiple signaling pathways related to reproductive hormones, steroid hormones receptors, intracellular regulators of oxidative stress and subsequent inflammation, apoptosis, and proliferation. Their role in the management of ovarian cancer, age-related reproductive insufficiency, ovarian ischemia, PCOS, or menopausal syndrome has been indicated. In particular, the potential involvement of grapeseed extracts and/or proanthocyanidin B2 and delphinidin on ovarian steroidogenesis, oocyte maturation, and developmental capacity has been implicated, albeit at different regulatory levels. Grape polyphenols exert a wide range of health benefits posing grape extract as an interesting and valuable dietary supplement for natural complementary therapy. This evidence-based study focuses on the actions of grapeseed extract and grape polyphenols on female reproductive processes at various regulatory levels and multiple signalling pathways by regulating reproductive hormones (GnRH, gonadotropins, prolactin, steroid hormones, IGFBP), steroid receptors, markers of proliferation and apoptosis. However, lack of knowledge of standardized dosages so far limits their clinical application despite the wide range of their biological and therapeutic potentials.